Comparison of Three Gestational Weight Gain Guidelines Under Use in Latin America - Mardones, Francisco; Rosso, Pedro; Erazo, Álvaro; Farías, Marcelo (Frontiers in Pediatrics, 2021)
Presently, three guidelines are used in Latin America to assess adequacy of maternal BMI during pregnancy: 1) the chart proposed by the Institute of Medicine of the United States (IOM), 2) the Rosso-Mardones Chart (RM), and 3) a modified RM chart proposed by Atalah et al (AEA). The aim of the present review was to explore available information on the sensitivity, specificity and both positive and negative predictive values of these charts to detect women at risk of delivering babies with the following signs of abnormal fetal growth: a) length at birth < 50 cm; (b) birth weight < 3000 g; and (c) birth weight ≥ 4000 g or 4250 g. Data from studies conducted in large samples of Chilean and Uruguayan women indicate that the RM chart has the greatest sensitivity to identify at risk cases. However, predictive values were similar for the three charts. Thus, the use of the RM chart should be preferred. The main limitation for using the IOM weight gain recommendations in Latin American women stems from the fact that their average height is approximately 20 cm lower than US women.